The Blessing Of Umkm Will Be “War Takjil” and Become A Symbol Of Tolerance In Ramadan Culture - Samawa Kantari; Febri Ashari; Endar Purnawan (SOUTHEAST ASIA JOURNAL oF GRADUATE OF ISLAMIC BUSINESS AND ECONOMICS, 2023)
This article discusses the blessings of UMKM on the existence of "war takjil" in the month of Ramadan. Based on the analysis of literature review and interviews, this study sheds light on the positive impact of war takjil in the month of Ramadan. This study reveals that in war takjil activities or competition to get takjil between Muslims and non-Muslims is not only one of the activities to enliven Ramadan, but also one way to maintain tolerance between religious communities. The results show that UMKM traders feel the benefits and unique stories when selling takjil where the buyers are not only Muslims but from across religions. In this takjil war, there is excitement, one of which is the panic expression of potential buyers when their favorite food is almost sold out so that the person concerned is desperate to break through the queue. Overall, the findings of this study underline that this moment is also a place to joke and have fun together. Competition in tajkil hunting does not mean hostility, instead it fosters mutual respect between religious communities, and becomes one of the events to strengthen the bond of brotherhood.